Reproducibility of the Whole-Brain N-Acetylaspartate Level across Institutions, MR Scanners, and Field Strengths - Benedetti, B.; Rigotti, D.J.; Liu, S.; Filippi, M.; Grossman, R.I.; Gonen, O. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Radiologic markers in multicenter trials are often confounded by different instrumentation used. Our goal was to estimate the variance of the global concentration of the neuronal cell marker N-acetylaspartate (NAA) among research centers using MR imaging scanners of different models, from different manufacturers, and of different magnetic field strength.MATERIALS AND METHODS: Absolute millimolar amounts of whole-brain NAA (WBNAA) were quantified with nonlocalizing proton MR spectroscopy in the brains of 101 healthy subjects (53 women, 48 men) aged 16–59 years (mean, 34.2 years). Twenty-three were scanned at 1 institute in a 1.5T Siemens Vision; 31 from another institute were studied with a 1.5T Siemens SP63; 36 were scanned at a third institute (24 with a 1.5T Vision, 12 with a 3T Siemens Trio); and 11 were obtained at a fourth institute using a 4T GE Signa 5.x. The NAA amounts were quantified with phantom-replacement and divided by the brain volume, segmented from MR imaging, to yield the concentration, a metric independent of brain size suitable for cross-sectional comparison.RESULTS: The average WBNAA concentration among institutions was 12.2 ± 1.2 mmol/L. The subjects’ WBNAA distributions did not differ significantly (p > .237) among the 4 centers, regardless of scanner manufacturer, model, or field strength and irrespective of whether adjustments were made for age or sex.CONCLUSION: Absolute quantification against a standard makes the WBNAA concentration insensitive to the MR hardware used to acquire it. This important attribute renders it a robust surrogate marker for multicenter neurologic trials.